ARRANGEMENT OF FLATS OWNERSHIP RIGHTS BY FOREIGN NATIONALS AFTER THE OMNIBUS LAW - Adhayaksa Putra, Prasetyo (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
This research aims to know How the above Property Rights arrangement apartment units in agrarian Tree Law and Apartment Law. Besides, this article analyzes the legality of foreign nationals in unit ownership apartment buildings from the perspective of omnibus law, fundamental agricultural law, and law about apartment buildings. The research method used in researchers this tian is a normative juridical method. In implementation research, the problem will be assessed based on the applicable norms or laws. The research found that legal certainty regarding man the registration of land for the construction of flats cannot be guaranteed by the omnibus law and other technical regulations, such as government regulation number 18 of 2021 concerning Management rights, land rights, apartment units, and land registration. The cause of not guaranteed ownership of land rights by foreign nationals is that the rules that applied previously have remained the same.